Optimalisasi Kerjasama Hexa-Helix Guna Mendukung Pengamanan Pemilu - Pratama, Bellen (Sekolah Tinggi Ilmu Kepolisian, 2023)
This paper is motivated by the urgency of maintaining political stability and security leading up to the 2024 elections, considering that several countries have experienced post-election conflicts. Although Indonesia's democracy tends to be better, the challenges of securing the 2024 elections are increasing. This research aims to optimize hexa-helix collaboration, which involves the government, business sector, academics, communities/NGOs, mass media, and aggregators, namely election organizers and participants, to enhance synergy in securing the 2024 elections. The research method used is descriptive-analytical, with data collected through observation, interviews, literature review, and SWOT analysis. The results indicate that the interaction among hexa-helix elements is not yet optimal, especially with academics, the business sector, mass media, and election participants. Ketapang Sub-regional Police have a central role in coordinating hexa-helix elements, although there are operational challenges and a need to enhance their role as regulators, facilitators, and catalysts.